FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2007 â 2009 - Delisa Natasia Putri, 08.05.51.0033; Irsad, Moch. (Students Journal of Economic and Management, 2012)
In the capital markets, the company is getting the funds is relatively inexpensive, because companies dont have to pay the capital costs or capital costs can be pressed. Securities which are often traded in the capital market is a stock. The shares are securities as evidence of the inclusion of or possession of individuals and institutions. Many factors can affect the price of stocks such as DER, ROA and research purposes PER. This is to know how the Debt to Equity Ratio (DER), Return On Assets (ROA) and the Price to Earning Ratio (PER) of stock price manufacturing companies in BEI. The population in this research the entire manufacturing company listed in BEI 2007% u2013. The sample in this research are 95